The Early Jewish Reception of Kantian Philosophy. (March 2022) - Hunter, Ian
Abstract : Current discussions of the early Jewish reception of Kantian philosophy are dominated by two major approaches. According to the first, this reception was governed by a universal Enlightenment rationalism that was present in Judaism no less than in Kantian philosophy. According to the second, it was the fact that Kantianism contained a latent Judaic kabbalistic philosophy that made it attractive to Jewish intellectuals. This paper departs from both approaches by showing that when Jewish intellectuals encountered Kantianism they found neither a universal rationality to which Judaism should conform, nor an esoteric Jewish metaphysics to which Kantian philosophy had already conformed, but something else entirely, namely a hostile philosophical religion that sought to reconstruct Judaism in its own image. As a result of the historical context in which this challenge arose, some Jewish intellectuals accepted this reconstruction as a rational reform, while others repudiated it as a Christian-rationalist assault on Jewish law and tradition. Characterized first by the absence of a defensive Jewish Schulmetaphysik that might combat Kantianism on its own grounds, and second by the preparedness of enlightened intellectuals to extort Jewish acceptance of Christian rationalism by withholding citizenship rights, this context made Kantian philosophy into an offer that was difficult for Jewish intellectuals to refuse, or accept.